Application Comparative of Java Plum (Syzygium cumini) Juice and Water On Jelly Drink - Fatma Wati, Ayu; Timur Ina, Putu; Sugitha, I Made (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 5 No 2 (2018): Scientific Journal of Food Technology (September), 2018)
The objective of this research were to observe the effect of java plum juice to the characteristic and appropriate treatment on jelly drink.The completely randomized design (CRD) with comparative treatment java plum juice and water six levels such us 10%:90%, 15%:85%, 20%:80%, 25%:75%, 30%; 70%, 35%:65% was use in the research. The data were analyzed through variance analysis and continued with Duncan`s Multiple Range Test (DMRT). The result showed that the ratio of java plum juice and water had a very significant effect to vitamin C, total anthocyanin, antioxidant activity (that IC50), color and texture (skor), color and taste (hedonic), and had a significant effect on flavor and texture (hedonic). Treatment of (35%:65%) the best characteristic of jelly drink, that give average value (vitamin C was 12,22 mg/100g, total anthocyanin was 4,87 mg/100g, antioxidant activity that determined by the value of IC50 was 96,24 mg/ml, color (purple) liked, taste (acid) rather liked, texture (mushy) plain, flavor plain, and overall acceptance rather liked) during storage at room temperature stability color of jelly drink decreased faster than that in refrigerator.